2020
DOI: 10.26706/ijaefea.3.7.20200806
|View full text |Cite
|
Sign up to set email alerts
|

Effect of FDM Process Parameters on the Mechanical Properties and Production Costs of 3D Printed PowerABS Samples

Abstract: The main objective of this study is to analyze of the effect of fused deposition modelling (FDM) printing process parameters on the mechanical properties, printing times and production costs of samples printed with Power Acrylonitrile Butadiene Styrene (PowerABS) filament using a three-dimensional (3D) printer. This study is primarily focused on the effects of the mechanical properties of 3D samples subjected to the influence of three factors; layer thickness (0.15, 0.2, and 0.25 mm), raster angle (15, 45, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The results reported that the 45° raster angle had the highest mechanical properties. The results also report optimum 3D printing process parameters for product cost were horizontal table orientation, 0.25 mm layer thickness, and 75° raster angle [18].…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…The results reported that the 45° raster angle had the highest mechanical properties. The results also report optimum 3D printing process parameters for product cost were horizontal table orientation, 0.25 mm layer thickness, and 75° raster angle [18].…”
Section: Introductionmentioning
confidence: 78%
“…In literature, filling structure, occupancy rate and table orientation are the most effective 3D printing parameters for the strength of products with 3D printing method [16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been conducted in the literature to examine the effect of 3D printing parameters on the mechanical properties of 3D printed products [47][48][49][50][51][52][53][54][55]. Kam et al [47] in their study produced six different filling test samples by keeping parameters such as the filling ratio, printing speed, layer thickness, filament, and nozzle diameter constant.…”
Section: Mechanical Properties Of Productsmentioning
confidence: 99%
“…However, the current polymer materials available for FDM 3D printing generally have some limitations for their wide application potential, including insufficient mechanical properties, poor heat resistance, low electrical conductivity or high production cost, which would affect the print quality and the further expansion of the application scenario. For some application conditions, these limitations are fatal [ 22 , 23 , 24 ]. To address these limitations, many solutions have been proposed.…”
Section: Introductionmentioning
confidence: 99%